Micropolitics and meritocracy: Improbable bed fellows?. (September 2019) - Montes López, Estrella; O'Connor, Pat
Universities present themselves as meritocratic organizations; however, there is evidence that such claims are 'rationalised myths'. This article is concerned with the perceived effect of micropolitics on academic careers in two case study universities: a collegial Spanish and a managerial Irish one. The data are drawn from 86 semi-structured interviews with academics (43 from each context). The focus is on two aspects of micropolitics: those related to career experiences, particularly networks; and those related to the evaluation of candidates, particularly double standards. Research results show that informal social networks are perceived to facilitate career progression; and these are referred to in particular by the Spanish male respondents. Double standards in evaluation are used to favour specific candidates: local ones in the Spanish case, men in the Irish case. Men in the Spanish context refer more openly than their Irish counterparts to these double standards, arguably reflecting the strength of discourses other than merit in that context. The results suggest that the informal structure influences the formal structure regardless of the governance model, raising fundamental questions about the nature of universities and the limitations of structural changes.